1991
DOI: 10.1007/bf00058901
|View full text |Cite
|
Sign up to set email alerts
|

Geology and tectonics of Beta Regio, Guinevere Planitia, Sedna Planitia, and Western Eistla Regio, Venus: Results from Arecibo image data

Abstract: New radar images (resolution 1.5-2.0 km) obtained from the Arecibo Observatory are used to assess the geology of a portion of the equatorial region of Venus (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

1991
1991
2000
2000

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 39 publications
(96 reference statements)
0
6
1
Order By: Relevance
“…Figure 3 is the fracture map, and Plate 1 is the regional geologic map. Many of the larger structures were visible in Arecibo radar and were described by Senske et al [1991].…”
Section: Mapping Proceduresmentioning
confidence: 95%
See 1 more Smart Citation
“…Figure 3 is the fracture map, and Plate 1 is the regional geologic map. Many of the larger structures were visible in Arecibo radar and were described by Senske et al [1991].…”
Section: Mapping Proceduresmentioning
confidence: 95%
“…Eistla Regio is a discontinuous series of rises striking roughly E-W between longitudes 340øE and 55øE at latitudes 10-25øN. It was characterized before Magellan by its substantial gravity anomaly [Sjogren et al, 1983] and volcanic and rift structures [Senske et al, 1991] as a likely hot spot. Further work on Eistla Regio is also given by Senske et al…”
Section: Introductionmentioning
confidence: 99%
“…The study of volcanism on Venus has provided insight into several of these questions and issues. Previous analyses of Venera lander data [Surkov et al, 1984[Surkov et al, , 1987, Earth-based radar data [Campbell et al, 1984Senske et al, 1991a, b] and data from Venera 15/16 [Barsukov et al, 1986;Barsukov and Volkov, 1989; Barsukov et al, 1992] have shown the abundance of volcanic deposits on Venus and the diversity and association of some volcanic edifices and smactures. However, image resolution was poorer than 1-3 km, and coverage was regional, rather than global.…”
Section: Introductionmentioning
confidence: 99%
“…The plains of Navka and Guinevere (Figure 1) consist primarily of bright and mottled plains, a southern extension of mottled plains mapped in the equatorial region to about 40" N (Senske, 1990;Senske et al, 1991). The mottled plains contain evidence for multiple flow units, some of which are associated with large edifices such as Ushas Mons and others of which are probably related to individual volcanic domes and shields as previously observed in central Guinevere Planitia (Campbell et al, 1989).…”
Section: Navka-guinevere Planitiaementioning
confidence: 60%
“…The new high-resolution radar images have allowed us to classify and map features and units in that part of the planet and compare their distribution and possible modes of origin with features in other parts of Venus. These data are also used to examine the geology of the Venus southern hemisphere and make comparisons with the northern high latitudes observed by Veneras 15/16 (Barsukov et al, 1986) and the equatorial region (Campbell et al, 1989;Senske, 1990;Senske et al, 1991).…”
Section: Geologic Mapping: Methods Unit Description and Unit Charactmentioning
confidence: 99%